Keeper of the gems - Quinn, Jordan (Quinn, Jordan. Kingdom of Wrenly, 2023)
The gnomes of the Stone Forest are in trouble when all the gems in the forest lose their shine, so Prince Lucas and Lady Clara help the gnomes before their home changes forever.